Low-hardness micro-foamed polyester elastomer composite material and preparation method and application thereof
By chemical crosslinking in TPEE resin and using MOFs material and sodium bicarbonate as foaming agents, the problem of uneven cell cells of existing soft microfoaming materials is solved, and a low-hardness microfoaming polyester elastomer composite material with uniform cell structure and excellent appearance is achieved.
Patent Information
- Application Number
- CN202411906153.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-04
AI Technical Summary
The existing soft micro foaming materials have uneven bubble cells during the foaming process, which leads to the appearance of foamed products that are prone to pitting, limiting their application in good-looking products.
Low-hardness micro-foaming polyester elastomer composite material is used to improve foaming performance by introducing isocyanate compounds into TPEE resin, and the foaming performance is improved by combining MOFs materials and sodium bicarbonate as foaming agents.
The uniform cell structure and excellent appearance of injection molded products are achieved, and the foaming effect is improved, making the cell more dense, the foaming rate is higher, and the mold opening can be performed at a large distance, achieving a good touch material with high foaming thickness and low surface hardness.
Smart Images

Figure CN119752120A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of foaming materials, and in particular relates to a low-hardness micro-foamed polyester elastomer composite material and a preparation method and application thereof. Background Art
[0002] Thermoplastic polyester elastomer (TPEE), also known as polyester rubber, is a type of linear block copolymer containing polyester hard segments and aliphatic polyester or polyether soft segments. Its application range has expanded from high elastic fibers in the early textile industry to automobiles, polymer alloys, biomedical materials, electronic appliances, films and other fields, becoming an indispensable new material.
[0003] In recent years, some soft micro-foam materials have been widely used in electronics, home appliances, automobiles, sports and leisure industries. However, the melt strength of TPEE is low, and the melt strength is further reduced after oil filling. It is difficult to lock the gas in the pores during the foaming process, which easily leads to uneven pores and pits on the appearance of foamed products, limiting its application in good-looking products. Therefore, the preparation of a soft and excellent-looking TPEE micro-foam material has broad application prospects. Summary of the invention
[0004] The purpose of the present invention is to provide a low-hardness micro-foamed polyester elastomer composite material and a preparation method and application thereof, so as to solve the problem that the existing soft micro-foamed materials have uneven pores and the foamed products are prone to have pits on their appearance.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] The low-hardness micro-foamed polyester elastomer composite material comprises the following raw materials in parts by weight:
[0007]
[0008]
[0009] The foaming agent is compounded from MOFs material and sodium bicarbonate.
[0010] Furthermore, the TPEE resin is polyether TPEE, and the isocyanate compound is a diisocyanate compound and / or a polyisocyanate compound.
[0011] Furthermore, the mass ratio of the MOFs material to sodium bicarbonate is 1:1.
[0012] Furthermore, the preparation steps of the MOFs material are:
[0013] Add the zirconium source and benzoic acid to N,N-dimethylformamide, stir evenly, then add 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene, transfer to a sealed container, heat to 110-120°C, keep for 24-48 hours, centrifuge, wash, soak, centrifuge and dry to obtain MOFs material.
[0014] Furthermore, in the above preparation step, the mass ratio of the zirconium source, benzoic acid, N,N-dimethylformamide and 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene is 3:50:180:1.
[0015] Furthermore, the zirconium source is ZrOCl2·8H2O or ZrCl4.
[0016] Furthermore, the cleaning solvent is N,N-dimethylformamide.
[0017] Furthermore, the soaking solvent is acetone.
[0018] Furthermore, the plasticizer is a low molecular weight polymer having a polar group and good compatibility with the TPEE resin, and is preferably No. 50 white oil.
[0019] Furthermore, the isocyanate compound is a mixture of one or more of diphenylmethane diisocyanate, toluene diisocyanate and naphthalene diisocyanate.
[0020] Furthermore, the lubricant is at least one of silicone masterbatch, polyethylene wax, stearate, ethylene bisstearamide, and grafted ethylene bisstearamide.
[0021] Furthermore, the anti-aging agent includes one or more of a primary antioxidant, an auxiliary antioxidant, an ultraviolet absorber and a light stabilizer.
[0022] The present invention provides a polyester elastomer injection micro-foam material, and its injection molded products have a uniform pore structure and excellent appearance. The initial hardness of the TPEE material is greatly reduced by high-temperature oil filling of the TPEE resin, and isocyanate compounds are further introduced to chemically cross-link with TPEE during the twin-screw extrusion process to form a network connection to avoid melt pulling and rupture, thereby avoiding the further reduction of the melt strength of the TPEE material and the deterioration of the foaming performance caused by the oil-filled plasticizer. In addition, adding a homemade foaming agent during the foaming process can further enhance the foaming effect of the material, making the pores denser, the foaming ratio higher, and being able to perform a large-distance mold opening action, achieving a high foaming thickness, low surface hardness, and good touch material.
[0023] The method for preparing the low-hardness micro-foamed polyester elastomer composite material comprises the following steps:
[0024] S1. Preparation of TPEE composite material: weigh TPEE resin, plasticizer, isocyanate compound, lubricant and anti-aging agent according to the proportion, stir to obtain a uniformly mixed material; put the uniformly mixed material into a parallel twin-screw extruder for melting, extrusion and granulation to obtain a TPEE composite material;
[0025] S2. Preparation of TPEE injection molding micro-foam material: physically mix the TPEE composite material and the foaming agent in S1; put the uniformly mixed material into an injection molding machine for melting and injection molding, and then open the mold for foaming to obtain a low-hardness micro-foam polyester elastomer composite material.
[0026] Furthermore, the barrel temperature of the parallel twin-screw extruder is 180-240° C., the screw speed is 500 r / min, the melt pressure is 2.0 MPa, and the vacuum degree is -0.1 MPa.
[0027] Furthermore, the barrel temperature of the injection molding machine is 220°C and the injection speed is 90 cm 3 / s, holding time 0s, mold temperature 60℃.
[0028] The low-hardness micro-foamed polyester elastomer composite material is used in the preparation of automobile interior decoration.
[0029] Beneficial effects of the present invention:
[0030] 1. The low-hardness micro-foamed polyester elastomer composite material prepared by the present invention can be recycled and reused to meet the development needs of green and recycled materials for automobiles.
[0031] 2. A low-hardness micro-foamed polyester elastomer composite material prepared by the present invention innovatively adds isocyanate compounds, which can undergo a certain chemical cross-linking reaction with TPEE during twin-screw extrusion to form a certain network connection, thereby avoiding melt tearing and rupture, thereby avoiding the disadvantages of further reducing the melt strength of the TPEE material and deteriorating the foaming performance due to the oil-filled plasticizer.
[0032] 3. A low-hardness micro-foamed polyester elastomer composite material prepared by the present invention, wherein the foaming agent is compounded by a MOFs material with an adsorption function and sodium bicarbonate. When sodium bicarbonate and the MOFs material are added to the TPEE resin at the same time, the MOFs material has a certain polarity and good compatibility with TPEE, so the sodium bicarbonate is well dispersed in the TPEE resin under the adsorption of the MOFs material. At the same time, the porous structure of the MOFs material can buffer the CO2 released by sodium bicarbonate when heated, and play an adsorption role in the process of CO2 desorption from TPEE, providing nucleation points, which is helpful for the homogenization of the pores, thereby improving the foaming performance of the TPEE composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] The present invention will be further described below in conjunction with the accompanying drawings.
[0034] Figure 1 This is a digital photo of the low-hardness micro-foamed polyester elastomer composite material obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] The present invention provides a low-hardness micro-foamed polyester elastomer composite material, comprising the following raw materials in parts by weight:
[0037]
[0038] The foaming agent is compounded from MOFs material and sodium bicarbonate.
[0039] The TPEE resin is polyether TPEE, and the isocyanate compound is a diisocyanate compound and / or a polyisocyanate compound.
[0040] The mass ratio of the MOFs material to sodium bicarbonate is 1:1.
[0041] The preparation steps of the MOFs material are:
[0042] Add the zirconium source and benzoic acid to N,N-dimethylformamide, stir evenly, then add 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene, transfer to a sealed container, heat to 110-120°C, keep for 24-48 hours, centrifuge, wash, soak, centrifuge and dry to obtain MOFs material.
[0043] In the above preparation steps, the mass ratio of the zirconium source, benzoic acid, N,N-dimethylformamide and 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene is 3:50:180:1.
[0044] The zirconium source is ZrOCl2·8H2O or ZrCl4.
[0045] The cleaning solvent was N,N-dimethylformamide.
[0046] The soaking solvent is acetone.
[0047] The plasticizer is a low molecular weight polymer with a polar group and good compatibility with the TPEE resin, and is preferably No. 50 white oil.
[0048] The isocyanate compound is a mixture of one or more of diphenylmethane diisocyanate, toluene diisocyanate and naphthalene diisocyanate.
[0049] The lubricant is at least one of silicone masterbatch, polyethylene wax, stearate, ethylene bisstearamide, and grafted ethylene bisstearamide.
[0050] The anti-aging agent includes one or more of a primary antioxidant, an auxiliary antioxidant, an ultraviolet absorber and a light stabilizer.
[0051] In some embodiments, the mass ratio of the primary antioxidant, the auxiliary antioxidant, the ultraviolet absorber and the light stabilizer in the antioxidant is 1:1:1:1.
[0052] In some specific embodiments, the primary antioxidant is a hindered phenol antioxidant, such as Irganox 565, RIANOX 330.
[0053] In some specific embodiments, the auxiliary antioxidant is a phosphite antioxidant, such as antioxidant 168 and PEP-36.
[0054] In some specific embodiments, the ultraviolet light absorber is a benzotriazole light absorber, such as UV-P.
[0055] In some specific embodiments, the light stabilizer is a hindered amine light stabilizer, such as LA-52 and UV-944.
[0056] The method for preparing the low-hardness micro-foamed polyester elastomer composite material comprises the following steps:
[0057] S1. Preparation of TPEE composite material: weigh TPEE resin, plasticizer, isocyanate compound, lubricant and anti-aging agent according to the proportion, stir to obtain a uniformly mixed material; put the uniformly mixed material into a parallel twin-screw extruder for melting, extrusion and granulation to obtain a TPEE composite material;
[0058] S2. Preparation of TPEE injection molding micro-foam material: physically mix the TPEE composite material and the foaming agent in S1; put the uniformly mixed material into an injection molding machine for melting and injection molding, and then open the mold for foaming to obtain a low-hardness micro-foam polyester elastomer composite material.
[0059] The barrel temperature of the parallel twin-screw extruder is 180-240° C., the screw speed is 500 r / min, the melt pressure is 2.0 MPa, and the vacuum degree is -0.1 MPa.
[0060] The barrel temperature of the injection molding machine was 220°C and the injection speed was 90 cm3 / s, holding time 0s, mold temperature 60℃.
[0061] The low-hardness micro-foamed polyester elastomer composite material is used in the preparation of automobile interior decoration.
[0062] The preparation process of the low-hardness micro-foamed polyester elastomer composite material is specifically described below through the following examples.
[0063] The raw materials used in the embodiments and comparative examples are as follows:
[0064] TPEE resin is a polyether polyester elastic, brand KYLf l ex L2520, melt index is 18g / 10min, manufacturer: Jiangsu Keyilai New Materials Co., Ltd.
[0065] The plasticizer is No. 50 white oil, brand No. 50 industrial white oil, manufacturer: Hengshui Diyi Petrochemical Co., Ltd.
[0066] Sodium bicarbonate, manufacturer: Suzhou Shengling Chemical Co., Ltd.
[0067] The lubricant is silicone masterbatch, brand MB50-002, manufacturer: Dow Corning, USA.
[0068] The antioxidant is composed of a primary antioxidant, an auxiliary antioxidant, an ultraviolet absorber and a light stabilizer in a mass ratio of 1:1:1:1.
[0069] The main antioxidant brand is Irganox 565, manufacturer: BASF, Germany.
[0070] Auxiliary antioxidant brand AN 168, manufacturer: Qingdao Deda Special Chemical Group.
[0071] Light absorber brand: Chi guard 5050, manufacturer: Qitai Co., Ltd.
[0072] Light stabilizer brand LA-52, manufacturer: Aidico (China) Investment Co., Ltd.
[0073] Preparation Example 1
[0074] The preparation steps of MOFs materials are as follows:
[0075] 0.3 g ZrOCl2·8H2O and 5 g benzoic acid were fully dissolved in 18 g N,N-dimethylformamide, and then 0.1 g 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene was added, transferred to a reactor, heated to 120°C and maintained for 24 h. After the reaction was completed, centrifuged at 8000 r / min, and washed with N,N-dimethylformamide at 8000 r / min. The precipitate was soaked in 50 mL acetone for 12 h, centrifuged at 8000 r / min, and maintained in a vacuum drying oven at 120°C for 12 h to obtain MOFs material, and the powder was light yellow.
[0076] Example 1
[0077] The preparation method of the low-hardness micro-foamed polyester elastomer composite material comprises the following steps:
[0078] S1. Add the MOFs material of Preparation Example 1 and sodium bicarbonate into a mixer at a mass ratio of 1:1, and mix at 500 rpm for 20 min to obtain a foaming agent.
[0079] S2. Take 70 parts of TPEE resin and 30 parts of No. 50 white oil by mass and fill them in an oven at 120℃ for 15 hours. Take them out after the oil is fully absorbed. Then add 1 part of silicone masterbatch, 1 part of diphenylmethane diisocyanate and 1 part of anti-aging agent, stir them at a speed of 500r / min for 10 minutes with a high-speed mixer to obtain a uniformly mixed material;
[0080] S3, putting the uniformly mixed material obtained in S2 into a parallel twin-screw extruder for melting, extrusion and granulation to obtain a TPEE composite material; wherein the barrel temperature of the parallel twin-screw extruder is 180-240°C, the screw speed is 500r / min, the melt pressure is 2.0MPa, and the vacuum degree is -0.1MPa;
[0081] S4. Add the TPEE composite material obtained in S3 and 6 parts of foaming agent into a high-speed mixer and mix them evenly, then put them into an injection molding machine for melting and injection molding to obtain a micro-foamed polyester elastomer composite material; the barrel temperature of the injection molding machine is 220°C and the injection speed is 90 cm 3 / s, holding time 0s, mold temperature 60℃.
[0082] The micro-foamed polyester elastomer composite material obtained in Example 1 was observed microscopically using a digital camera. Figure 1 As shown by Figure 1 It can be seen that the cells of the micro-foamed polyester elastomer composite material prepared in this embodiment are uniform and continuous.
[0083] Example 2
[0084] The method for preparing the low-hardness micro-foamed polyester elastomer composite material is different from that in Example 1, only in that the amount of the foaming agent in step S4 is adjusted from 6 parts by mass to 5 parts by mass.
[0085] Example 3
[0086] The method for preparing the low-hardness micro-foamed polyester elastomer composite material is different from that in Example 1, only in that the amount of the foaming agent in step S4 is adjusted from 6 parts by mass to 4 parts by mass.
[0087] Example 4
[0088] The preparation method of the low-hardness micro-foamed polyester elastomer composite material is different from that of Example 1 only in step S2. The specific operation of step S2 in this embodiment is as follows:
[0089] By mass, 75 parts of TPEE resin and 25 parts of No. 50 white oil were added to an oven at 120°C for 15 hours, and the oil was taken out after being fully absorbed. Then, 1 part of silicone masterbatch, 1 part of diphenylmethane diisocyanate and 1 part of anti-aging agent were mixed with a high-speed mixer at a speed of 500r / min for 10 minutes to obtain a uniformly mixed material.
[0090] Example 5
[0091] The preparation method of the low-hardness micro-foamed polyester elastomer composite material is different from that of Example 1 only in step S2. The specific operation of step S2 in this embodiment is as follows:
[0092] By mass, 80 parts of TPEE resin and 20 parts of No. 50 white oil were added to an oven at 120°C for 15 hours, and the oil was taken out after being fully absorbed. Then, 1 part of silicone masterbatch, 1 part of diphenylmethane diisocyanate and 1 part of anti-aging agent were mixed with a high-speed mixer at a speed of 500r / min for 10 minutes to obtain a uniformly mixed material.
[0093] Comparative Example 1
[0094] The method for preparing the low-hardness micro-foamed polyester elastomer composite material is different from that in Example 1 only in step S2. The specific operation of step S2 in this comparative example is as follows:
[0095] Take 100 parts of TPEE resin, 1 part of silicone masterbatch, 1 part of diphenylmethane diisocyanate and 1 part of antioxidant by mass, and stir them at a speed of 500 r / min for 10 minutes with a high-speed mixer to obtain a uniformly mixed material.
[0096] Comparative Example 2
[0097] The method for preparing the low-hardness micro-foamed polyester elastomer composite material is different from that in Example 1 only in step S2. The specific operation of step S2 in this comparative example is as follows:
[0098] By mass, take 70 parts of TPEE resin and 30 parts of No. 50 white oil and put them in an oven at 120℃ for 15 hours. After the oil is fully absorbed, take them out. Then add 1 part of silicone masterbatch and 1 part of anti-aging agent, stir them at a speed of 500r / min for 10 minutes with a high-speed mixer to obtain a uniformly mixed material.
[0099] Comparative Example 3
[0100] The preparation method of the low-hardness micro-foamed polyester elastomer composite material is different from that of Example 1 only in step S4. The specific operation of step S4 in this comparative example is:
[0101] The TPEE composite material obtained in S3 and 3 parts of sodium bicarbonate were added to a high-speed mixer and mixed, and then put into an injection molding machine for melting and injection molding to obtain micro-foamed polyester elastomer composite materials of different thicknesses; the barrel temperature of the injection molding machine was 220°C and the injection speed was 90 cm 3 / s, holding time 0s, mold temperature 60℃.
[0102] The amount of each component added during the preparation of the low-hardness micro-foamed polyester elastomer composite material of Examples 1 to 5 and Comparative Examples 1 to 3 was statistically analyzed, as shown in Table 1;
[0103] Table 1
[0104]
[0105] The low-hardness micro-foamed polyester elastomer composite materials obtained in Examples 1 to 5 and Comparative Examples 1 to 3 were tested, and the results are shown in Table 2:
[0106] Table 2
[0107]
[0108]
[0109] Note: The initial thickness of the product is 1.8mm. The hardness is the performance index of the material after foaming, and the foaming ratio represents the foaming capacity of the material.
[0110] From the test results of Examples 1 to 5 and Comparative Examples 1 to 3 in Table 2, it can be seen that the TPEE foaming material prepared without adding No. 50 white oil in Comparative Example 1 has a low ratio, high hardness, poor touch, and is difficult to meet the use requirements of automotive soft interiors. Comparative Example 2 has a poor state of pores after foaming due to the lack of a cross-linked structure, and is prone to local pores. Comparative Example 3 has poor CO2 desorption capacity and a low foaming ratio due to the lack of foaming nucleation sites provided by the MOFs carrier for ammonium bicarbonate. By adding isocyanate compounds, sodium bicarbonate and MOFs carriers, the samples of Examples 1 to 5 show the characteristics of low hardness, high foaming ratio, and continuous and uniform pores, and have good foaming effects, thereby meeting the use requirements of automotive soft interiors. In addition, the addition of silicone masterbatch is conducive to product demoulding and improves processing efficiency. The addition of anti-aging agents gives the micro-foamed material better weather resistance, meeting the use requirements of environments such as light and high temperature.
[0111] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0112] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A low-hardness micro-foamed polyester elastomer composite material, characterized in that: It includes the following raw materials in parts by weight: The foaming agent is compounded from MOFs material and sodium bicarbonate.
2. The low-hardness micro-foamed polyester elastomer composite material according to claim 1, characterized in that: The mass ratio of the MOFs material to sodium bicarbonate is 1:
1.
3. The low-hardness micro-foamed polyester elastomer composite material according to claim 1, characterized in that: The TPEE resin is polyether TPEE, and the isocyanate compound is a diisocyanate compound and / or a polyisocyanate compound.
4. The low-hardness micro-foamed polyester elastomer composite material according to claim 1 or 2, characterized in that: The preparation steps of the MOFs material are: Add the zirconium source and benzoic acid to N,N-dimethylformamide, stir evenly, then add 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene, transfer to a sealed container, heat to 110-120°C, keep for 24-48 hours, centrifuge, wash, soak, centrifuge and dry to obtain MOFs material.
5. The low-hardness micro-foamed polyester elastomer composite material according to claim 4, characterized in that: The mass ratio of zirconium source, benzoic acid, N,N-dimethylformamide and 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene is 3:50:180:
1.
6. The low-hardness micro-foamed polyester elastomer composite material according to claim 4, characterized in that: The zirconium source is ZrOCl2·8H2O or ZrCl4.
7. The low-hardness micro-foamed polyester elastomer composite material according to claim 1, characterized in that: The plasticizer is No. 50 white oil.
8. The low-hardness micro-foamed polyester elastomer composite material according to claim 1 or 3, characterized in that: The isocyanate compound is a mixture of one or more of diphenylmethane diisocyanate, toluene diisocyanate and naphthalene diisocyanate.
9. The method for preparing the low-hardness micro-foamed polyester elastomer composite material according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Stirring TPEE resin, plasticizer, isocyanate compound, lubricant and anti-aging agent to obtain a uniformly mixed material; putting the uniformly mixed material into a parallel twin-screw extruder for melting, extrusion and granulation to obtain a TPEE composite material; S2, physically mixing the TPEE composite material and the foaming agent in S1; putting the uniformly mixed materials into an injection molding machine for melting and injection molding, and then opening the mold for foaming to obtain a low-hardness micro-foamed polyester elastomer composite material.
10. Use of the low-hardness micro-foamed polyester elastomer composite material according to any one of claims 1 to 8 in the preparation of automobile interior decoration.
Citation Information
Cited By
Polyisocyanurate low-temperature thermal insulation material
CN122302207A